Analysis of the Business Process in Uzbek Tourism and Application of Digitalization to Solve the Problem - Naimzoda, Bayramova Muattar; Samatovich, Sobirjon Ruziyev (International Journal on Orange Technologies, 2023)
This scientific article describes the importance of the analysis of the business process in Uzbek tourism and the introduction of innovative technologies in solving problems in it, in particular, the use of digitalization in improving the quality of Service.